Emergence of a Shīʿī Islamic Environmental Paradigm: Legal and Ethical Considerations = ṣīāġa nmūḏǧ bīīʾī āʾslāmī šīʿī: ālāʿtbārāt ālšrʿīa ūālāʾḫlāqīa - Speidl, Bianka (Journal of Islamic ethics, 2025)
This article examines the emerging environmental discourse in contemporary Shīʿī Islam, analysing works across traditional fiqh (Islamic jurisprudence), environmental jurisprudence (fiqh al-bīʾa), and environmental theology. It traces the evolution of Shīʿī approaches to the environment from conventional juristic rulings to more holistic frameworks integrating philosophy, ethics, and scientific knowledge. The study analyses works by Muḥammad Bāqir al-Ṣadr (d. 1980), Luṭf Allāh Ṣāfī Gulpāygānī (d. 2022), Āyat Allāh Muḥammad al-Ḥusaynī al-Shīrāzī (d. 2001), Sayyid Ḥusayn Aḥmad al-Khishn (b. 1966), and Āyat Allāh Muṣṭafā Muṣṭafā Muḥaqqiq Dāmād (b. 1945), examining the evolving relationship between fiqh and akhlāq (ethics) in Shīʿī environmental discourse. It is argued that in its recent developments, a distinctive Shīʿī contribution to Islamic environmental thought is characterised by a transformative shift towards an interdisciplinary understanding of environmental problems by combining juristic, philosophical, and theological perspectives - deeply embedded in the Shīʿī tradition. The article concludes by assessing the potential of this emerging discourse in relation to Shīʿī communities and for Islamic approaches to environmental ethics.